Selected Papers from the pHealth 2021 Conference, Genoa, Italy, 8-10 November 2021 - Blobel, Bernd; Giacomini, Mauro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint addresses healthcare transformation towards personalized, participative, preventive, predictive, and precision medicine (5P Medicine) with the support of new technologies such as micro-, nano-, and bio-techniques, as well as artificial intelligence and learning systems. It focuses, therefore, on the representation and management of knowledge from different domains and their actors, using their methodologies and languages but also individual skills and experiences. The outcome is a system-oriented, architecture-centric, ontology-based, policy-driven approach allowing a formal representation and management of health ecosystems, including their integration and interoperability. Such development is accompanied by security, privacy, and ethical challenges to be resolved. The reprint describes the principles, methodologies, and standards for successfully managing the transformation of health and social care, illustrated by many practical examples and implemented use cases. The reprint is based on papers published in the context of the pHealth 2021 Conference in Genoa, Italy. However, the content goes far beyond the focus and size of the original papers.